Development of Non Hosted Custom Domain Websites As a Learning Medium to Improve Learning Outcomes - Rufii (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Learning media plays an important role in the learning process, especially in concrete courses. The use of easy, dynamic and interesting media can have an effect on students to learn compared to boring conventional learning media so that it is necessary to develop new media that can overcome these problems. The purpose of this study is to determine the feasibility and effectiveness of learning media in the form of non-hosted custom domain websites to improve learning outcomes. This research uses a research and development method with a 5-stage ADDIE development model. In the results of the feasibility test, media experts obtained a score with a percentage of 81.33% with a very decent category, while material experts obtained a score with a percentage of 89.33% with a very decent category. The results of the trial on 25 graduate students obtained a percentage of 92% with a very decent category. The increase in learning outcomes above KKM 75 after using non-hosted custom websites reached 84% from the previous 20% so that it can be concluded that the use of non-hosted custom domain websites on learning media can improve learning outcomes. The new findings in this study are in the form of the use of websites that are usually used paid for education, now it is easier and cheaper to use non-hosted websites that are custom domains using the teacher's own name, so that the use of the teacher's name can increase credibility in the world of education, especially in cyberspace. Keywords: Learning Media, Non hosted Website, Improve Learning Outcome